2016
DOI: 10.3390/ma9040233
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Fabrication of High-Aspect-Ratio Platinum Microprobes by Electrochemical Discharge Etching

Abstract: Using a graphite crucible as the counter-electrode, platinum microprobes with an aspect ratio of 30 and a tip apex radius less than 100 nm were fabricated by an electrochemical discharge etching process. The “neck-in” structure on the platinum wire induced by the electrical discharge at the liquid-air interface plays a key role in the probe shape and the voltage of the following pure electrochemical etching determines the final probe aspect ratio and tip dimensions. Moreover, the shape and diameter of the grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In the setup, an electrochemically etched Platinum–Iridium (Pt/Ir) wire of 127 m diameter was composed of 20 %wt. Ir (Alfa Aesar) microprobe was produced with an adopted method described by Zhang et al 43 and Khan et al 44 . The Pt/Ir microprobe was installed on a nanomanipulator (Kleindiek MM3A) attached to the XY-stage of an optical microscope (Nikon Optiphot 100).…”
Section: Resultsmentioning
confidence: 99%
“…In the setup, an electrochemically etched Platinum–Iridium (Pt/Ir) wire of 127 m diameter was composed of 20 %wt. Ir (Alfa Aesar) microprobe was produced with an adopted method described by Zhang et al 43 and Khan et al 44 . The Pt/Ir microprobe was installed on a nanomanipulator (Kleindiek MM3A) attached to the XY-stage of an optical microscope (Nikon Optiphot 100).…”
Section: Resultsmentioning
confidence: 99%
“…25) Zhang and Lian discussed the behavior during the AC tip etching. 26) Vitus et al showed the light emission spectra of sparking during the etching and confirmed all the elements in the etching process. 27) Libioulle et al conducted additional micro polishing with H 2 SO 4 aq.…”
Section: Introductionmentioning
confidence: 92%
“…As a result, the electrode potential decreases and deviates from the expected electrode potential, leading to electrochemical polarization. [26][27][28] Extensive experimental analyses have demonstrated that an etching voltage of 13 V is optimal, resulting in the smallest achievable radius at the tip of the platinum wire. After the etching process, probes were cleaned with deionized water to 026501-2…”
Section: Fabrication Of the Probementioning
confidence: 99%